The Use of PowToon As Media to Reduce Teacher’s Anxiety in Teaching EFL Class - Made Satya Raditya; Putu Enik Kristiani (Acitya: Journal of Teaching and Education, 2022)
In improving the quality of teaching, several factors must be to pay attention to. One of the factors at issue is anxiety, which is a significant problem in the classroom. Anxiety often occurs in inexperienced teachers. It makes teaching ineffective in terms of providing information to students. The consequences of anxiety in learning have an impact on discomfort in learning. With today's developing technology, this problem can be reduced, especially on the anxiety factor in the learning process. This study aimed to identify the effectiveness of using the PowToon application in reducing teacher anxiety in teaching EFL classes. This literature study used eight papers studying the effect of the use of PowToon and similar E-media in teaching. The findings of this study indicate that PowToon provides many advantages in learning. Because PowToon is one of the media that can make it easier for teachers to teach and explain. With the help of PowToon, the application can also make students innovative because learning does not feel bored with monotonous learning situations. The findings show that using media with PowToon can reduce anxiety, increase teacher confidence, and make learning more enjoyable. Thus, this research can provide information for teachers who has less confidence in teaching